Mudo Barapi: Vivid Young Spirit - Astri Novrita Nababan; Budiwirman Budiwirman (Pascasarjana, Universitas Negeri Padang, 2021)
This article aimed to describe the form, inheritance, and preservation of the art of randai performed by the randai group Mudo Barapi, Solok, West Sumatra. This research used a qualitative approach with descriptive methods. The data collection technique was done by using the literature study, observation, interview, and documentation. The results showed that in the current era of globalization, the art of randai is less attractive to the younger generation. However, the randai group, Mudo Barapi, established in 2010 until now, has attracted the younger generation to join and love randai. The Mudo Barapi randai group presents a form of randai performance that follows the times. The Mudo Barapi randai group presents a form of randai creation in its appearance, but it does not eliminate the main elements of tradition in randai. The performance form of the Mudo Barapi randai group is packaged differently, starting from the duration of the performance, the variations in the form of movements, to the speed of the movements created in such a way as to make it look attractive to the audience. In the process of inheriting randai to its members, the founder has his tricks that are rarely done by others. It makes the Mudo Barapi randai group exist and have a place in society to this day.